Development of Interactive Video Media to Improve Students' Speaking Skills - Halimatussa’diyah, Halimatussa’diyah; Hartono, Hartono; Sudiran, Sudiran (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study intends to identify the requirements of students and teachers for enhancing speaking skills and validate the use of interactive video in the classroom. This study used the ADDIE model's research and development (R&D) methodology: analysis, design, development, implementation, and evaluation. Thus, it validated the teacher's material requirements and analyzed the students' needs. This study includes three English instructors and 18 secondary school students from MTS Miftahul Ulum Lumajang. Observation of classes, interviews, and questionnaires were utilized to collect data for this study. However, an interview revealed that the teacher frequently encountered difficulties devising English material for the junior high school class, particularly for the eighth grade, due to students' asking and expressing opinions. This study revealed, through a questionnaire, that the majority of teachers (66.7%) had difficulty enhancing students' speaking abilities by asking and giving opinions. This study revealed that the majority of students (72.2%) struggle to develop their speaking skills through asking and responding. Therefore, interactive video must be utilized. This study has provided the majority of teachers with a positive perspective on the effectiveness of interactive videos in enhancing speaking proficiency.